2009
DOI: 10.5194/os-5-47-2009
|View full text |Cite
|
Sign up to set email alerts
|

Turbulence closure: turbulence, waves and the wave-turbulence transition – Part 1: Vanishing mean shear

Abstract: Abstract. This paper extends a turbulence closure-like model for stably stratified flows into a new dynamic domain in which turbulence is generated by internal gravity waves rather than mean shear. The model turbulent kinetic energy (TKE, K) balance, its first equation, incorporates a term for the energy transfer from internal waves to turbulence. This energy source is in addition to the traditional shear production. The second variable of the new two-equation model is the turbulent enstrophy ( ). Compared to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…Once Γ m is known, it can be used to determine the vertical eddy viscosity, A z , to estimate mixing. It has been shown that when Ri > 0.5, turbulence is completely suppressed by stratification and turned into wave energy (Baumert & Peters, ). However, Giddings et al () found this threshold to be as high as 1 in the Snohomish River.…”
Section: Methodsmentioning
confidence: 99%
“…Once Γ m is known, it can be used to determine the vertical eddy viscosity, A z , to estimate mixing. It has been shown that when Ri > 0.5, turbulence is completely suppressed by stratification and turned into wave energy (Baumert & Peters, ). However, Giddings et al () found this threshold to be as high as 1 in the Snohomish River.…”
Section: Methodsmentioning
confidence: 99%
“…When estimating R i , constraints were taken into consideration regarding the limiting value of Ri . Baumert and Peters [] demonstrated that turbulence does not exist when R i > 0.5 because TKE is converted to wave energy. Following the method of Ilicak et al .…”
Section: Methodsmentioning
confidence: 99%
“…The turbulent mixing layer in the lower part of the Earth's atmosphere has an important role in the vertical transport of moisture, small gas constituents, pollutants, and heat from the surface to the upper layers of the atmosphere. The turbulent mixing layer height is usually understood to be the thickness of the layer adjacent to the ground, in which in-coming substances become completely vertically distributed throughout the layer owing to convection or turbulence for an hour (Stull, 1988;Garratt, 1994;Bonin et al, 2018). Among other factors (Garratt, 1994), the mixing layer height strongly depends on the intensity of wind turbulence.…”
Section: Introductionmentioning
confidence: 99%